Azriyau of Yaudi - Tadmоr, Hayyim (1961)
= Azariah of Judah in Assyrian Inscriptions: Malamat A. (ed.), The Kingdoms of Istrael and Judah (Jerusalem 1961) 158-93 (2 figs.) (in Hebrew: English summary, p. XIV).